Lipid microdomain modification sustains neuronal viability in models of Alzheimer’s disease - Herzer, Silke; Meldner, Sascha; Rehder, Klara Franziska; Gröne, Hermann-Josef; Nordström, Viola (Acta Neuropathologica Communications, 2017)
Decreased neuronal insulin receptor (IR) signaling in Alzheimer’s disease is suggested to contribute to synaptic loss and neurodegeneration. This work shows that alteration of membrane microdomains increases IR levels and signaling, as well as neuronal viability in AD models in vitro and in vivo. Neuronal membrane microdomains are highly enriched in gangliosides. We found that inhibition of glucosylceramide synthase (GCS), the key enzyme of ganglioside biosynthesis, increases viability of cortical neurons in 5xFAD mice, as well as in cultured neurons exposed to oligomeric amyloid-β-derived diffusible ligands (ADDLs). We furthermore demonstrate a molecular mechanism explaining how gangliosides mediate ADDL-related toxic effects on IR of murine neurons. GCS inhibition increases the levels of functional dendritic IR on the neuronal surface by decreasing caveolin-1-mediated IR internalization. Consequently, IR signaling is increased in neurons exposed to ADDL stress. Thus, we propose that GCS inhibition constitutes a potential target for protecting neurons from ADDL-mediated neurotoxicity and insulin resistance in Alzheimer’s disease.
Gesehen am 13.05.2020